Determinants of wearer satisfaction factors for harnesses in upper-limb assistive wearable robots - U Ri Chae; Gi Hyun Lee; Hongbum Kim; Kyujung Kim; Jongkyu Choi; Dong Jin Hyun; Jungmin Yun (Heliyon, 2024)
Wearable robots are increasingly being deployed for use in industrial fields. However, only a few studies have focused on the usability of wearable robots. The present study evaluated the factors affecting the usability of a harness in securing a wearable robot to the body because the harness directly affects the work efficiency, and thus its design and use require careful consideration. A comparative evaluation of the arrangement of the Vest Exoskeleton before and after improvements was conducted, in which participants performed a benchmark assembly task while wearing the robot. Results showed that wearability decreased after the improvements due to the additional straps and buckles used, but the overall wearing satisfaction improved as a result of increased stability. Stability and convenience were the main factors affecting the overall wearing satisfaction, while sub-indicators included wearing comfort and tactile sensation. Therefore, improvements in stability, such as those related to fixation strength and tactile sensation, had a direct positive impact on the overall wearing satisfaction.